Aedes (Aedes) cinereus Meigen 1818 - Khalin, A. V.; Aibulatov, S. V. (Zenodo, 2021)
Aedes ( Aedes ) cinereus Meigen, 1818 Northernmost records (Fig. 2b). 68°49 ′ N, 32°42 ′ E, MP, Kol’skiy Distr., Tuloma (Sharkov, 1976); 67°29 ′ 16.02 ″ N, 51°52 ′ 52.23 ″ E, NAR, Zapolyarnyy Distr., Kamenka (Monchadsky, 1950); 66°40 ′ 29.09 ″ N, 62°33 ′ 56.46 ″ E, Komi, Vorkuta Distr., Sivaya Maska (Panyukova & Ostroushko, 2017). Distribution . NWR: AP, Komi, KP, LP, MP, NAR, NP, PP, RK, SPb, VP. Adjacent countries: Norway, Sweden, Finland, Estonia, Latvia, Lithuania and Belarus. Europe (ranging northward to the UK, Belgium, Netherlands and Denmark), European Russia, Siberia, Russian Far East including Sakhalin Island and Kamchatka Peninsula, Transcaucasia, Central Asia, North America. Published as part of Khalin, A. V. & Aibulatov, S. V., 2021, Northernmost records of mosquito species (Diptera: Culicidae) in northwestern Russia, pp. 46-63 in Zoosystematica Rossica (Zoosyst. Rossica) (Zoosyst. Rossica) 30 (1) on page 51, DOI:10.31610/zsr/2021.30.1.46, http://zenodo.org/record/10124237